2009
DOI: 10.1016/j.neuropsychologia.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Action naming is impaired in Parkinson disease patients

Abstract: In order to explore the possible contribution of the motor system to the representation of verbs, we studied the relative preservation of the capacity of Parkinson disease patients to name matched sets of object and action pictures. The performance of this group of participants was compared with that of a group of healthy seniors, and a group of Alzheimer disease patients. Generalized linear mixed-effects analyses showed that, whereas the two control groups had similar accuracy scores in response to objects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 24 publications
7
56
0
1
Order By: Relevance
“…The dorsal angular gyrus, which corresponds to our present findings, has been proposed as functional subdivision involved in searching for semantic information (Seghier, Fagan, & Price, 2010) and bottom‐up semantic processing (Whitney, Grossman, & Kircher, 2009). Semantic processing difficulties have been documented in PD, even in the absence of dementia or cognitive impairment (Boulenger et al., 2008; Roberts et al., 2017; Rodriguez‐Ferreiro, Menendez, Ribacoba, & Cuetos, 2009; Signorini & Volpato, 2006). As longitudinal changes in UPDRS Part III speech impairment scores have been shown to correlate with impaired semantic verbal fluency in PD (Gago et al., 2009), it is possible that elevated connectivity between left GPi and bilateral angular gyrus reflects differences in semantic processing between PDN and PDSI groups.…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal angular gyrus, which corresponds to our present findings, has been proposed as functional subdivision involved in searching for semantic information (Seghier, Fagan, & Price, 2010) and bottom‐up semantic processing (Whitney, Grossman, & Kircher, 2009). Semantic processing difficulties have been documented in PD, even in the absence of dementia or cognitive impairment (Boulenger et al., 2008; Roberts et al., 2017; Rodriguez‐Ferreiro, Menendez, Ribacoba, & Cuetos, 2009; Signorini & Volpato, 2006). As longitudinal changes in UPDRS Part III speech impairment scores have been shown to correlate with impaired semantic verbal fluency in PD (Gago et al., 2009), it is possible that elevated connectivity between left GPi and bilateral angular gyrus reflects differences in semantic processing between PDN and PDSI groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, action-verb deficits in PD have been attributed to underlying inhibitory control (Copland, 2003) or working memory (WM) (Colman et al, 2009) deficits. However, the non-demented PD patients tested by Rodriguez-Ferreiro et al (2009) exhibited significant impairments in action (but not in object) naming without concurrent executive impairment. Similarly, the early PD patients assessed by Ibáñez et al (2013) evinced deficits in both action semantics and the ability to integrate action-verb and motor information, but these deficits were not associated with executive or general cognitive impairment.…”
Section: Introductionmentioning
confidence: 89%
“…Given this symptom profile, PD offers an appropriate framework to examine the relation between bodily motion and action language. naming [27,28], verbal fluency [29], related-word production [30]). Other reports have found that PD patients exhibiting difficulties in both actionverb and noun processing were more impaired in the former during word naming [31] and word generation [32], and that they improved action naming more than object naming upon stimulation of the subthalamic nucleus [33].…”
Section: Action-language Impairments In Parkinson's Diseasementioning
confidence: 99%